2020
DOI: 10.1002/asia.202000278
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Supported FeP‐CoMoP Hierarchical Nanostructures for Efficient Hydrogen Evolution

Abstract: Fabricating highly efficient electrocatalysts for electrochemical hydrogen generation is a top priority to relief the global energy crisis and environmental contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…For comparison, the overpotential of CoMo/CoMoP/NF (104 mV) with greater advantage at 100 mA cm –2 is also shown in Figure b. What is more, the as-prepared CoMo/CoMoP/NF still shows superior activity compared with other recently reported advanced metal/metal phosphide electrocatalysts (Figure h), such as Mo-CoP (40 mV), Co-Mo-B-P/CF (48 mV), CoP/MoP@NC/CC (94 mV), and so on, ,,,,,, which indicates that this alloy/phosphide heterostructure electrocatalyst has a unique advantage in high HER activity. As expected, Figure c shows that the corresponding Tafel slopes of Pt/C (30.8 mV dec –1 ) are almost equal to the results of previous studies. , The Tafel slope of CoMo/CoMoP/NF is 46.4 mV dec –1 and is lower than those of CoMo/CoMo-LDH/NF, CoMo/NF, CoMoP/NF, CoMo-LDH/NF, and Co-MOF/NF, which reveals that the CoMo/CoMoP/NF undergoes the Volmer–Heyrovsky reaction.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…For comparison, the overpotential of CoMo/CoMoP/NF (104 mV) with greater advantage at 100 mA cm –2 is also shown in Figure b. What is more, the as-prepared CoMo/CoMoP/NF still shows superior activity compared with other recently reported advanced metal/metal phosphide electrocatalysts (Figure h), such as Mo-CoP (40 mV), Co-Mo-B-P/CF (48 mV), CoP/MoP@NC/CC (94 mV), and so on, ,,,,,, which indicates that this alloy/phosphide heterostructure electrocatalyst has a unique advantage in high HER activity. As expected, Figure c shows that the corresponding Tafel slopes of Pt/C (30.8 mV dec –1 ) are almost equal to the results of previous studies. , The Tafel slope of CoMo/CoMoP/NF is 46.4 mV dec –1 and is lower than those of CoMo/CoMo-LDH/NF, CoMo/NF, CoMoP/NF, CoMo-LDH/NF, and Co-MOF/NF, which reveals that the CoMo/CoMoP/NF undergoes the Volmer–Heyrovsky reaction.…”
Section: Resultsmentioning
confidence: 76%
“…As shown in the further magnified HRTEM images, the distinct lattice fringes with a spacing of 2.13 Å correspond to interplanar distances of the CoMo (111) plane (Figure f1, f2) . Moreover, the lattice spacings of 2.31 and 2.84 Å can be assigned to the (112) and (111) planes of CoMoP (Figure f3,f4), respectively. , The EDS results show the presence of Co, Mo, and P elements (Figure S4), and the proportion of elements is in general agreement with the ICP test results (Table S1). The scanning transmission electron microscopy-high-angle annular dark-field (STEM-HAADF) and the elemental mappings of CoMo/CoMoP/NF show an overall homogeneous distribution of Co, Mo, and P elements across the nanosheet as well as a concentration of Co and Mo elements in the region of the alloy particles (Figure g).…”
Section: Resultsmentioning
confidence: 83%
“…27 Specifically, the best catalytic activity can be obtained when the catalyst has a ΔG H* value close to zero. 58,59 The results showed that the ΔG H* value of Co 2 P/CoMoP 2 (0.16 eV) is much closer to the ideal value, as compared to those of Co 2 P (0.75 eV) and CoMoP 2 (1.59 eV) (Fig. 8b).…”
Section: Dft Calculationsmentioning
confidence: 75%
“…[26] The peaks located at 133.7 eV and 134.6 eV can be ascribed to 2p 3/2 and 2p 1/2 of PÀ O, respectively. [27] In the highresolution Fe 2p XPS spectrum (Figure 1 f), the doublet located at 707.3 eV and 720.1 eV can be assigned to 2p 3/2 and 2p 1/2 of Fe δ + , respectively, which corresponds to Fe in FeP. As shown in Figure 1e and f, the corresponding characteristic peaks of PÀ Fe were annotated, and Ov-Fe 2 O 3 phosphide contained a stronger PÀ Fe peak than p-Ov-Fe 2 O 3 phosphide.…”
Section: Resultsmentioning
confidence: 99%